Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 1533946125 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "Year 1991-2022" ] } The dataset includes 1533946125 records from 25262 constituent datasets: 1127 records from marine sediment metagenome Metagenome. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 68 records from Streuobstwiese. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 14 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 8 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1645460 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 5 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 1629 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 7 records from Virotia azurea (Proteaceae: Macadamieae), a striking new species endemic to New Caledonia and notes on V. francii and V. leptophylla. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4616 records from Inventaire de la flore du Grand Poitiers 2009. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 5963 records from University of Guam Insect Collection. 15 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1459 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 8 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 5 records from Hydromedusae observed during night dives in the Gulf Stream. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 760 records from UWIZM Molluscs. 1 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 3941 records from MCP-Aves - Coleção de Aves. 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 33 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 263 records from Bird specimens of Saitama Museum of Natural History. 36 records from orthopteracollections-nhmj-ioj. 1 records from Review of the millipede tribe Polydrepanini, with the description of a new species from Kerala state, southern India (Diplopoda, Polydesmida, Paradoxosomatidae, Alogolykinae). 3 records from Vasopora ceramica n. gen., n. sp. - a new abyssal cyclostome bryozoan from polymetallic nodules in the Russian exploration area, Clarion-Clipperton Fracture Zone, eastern Pacific Ocean. 16 records from Insect Collections of Okomu National Park- Nigeria. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 215119 records from ARABEL - Arachnologia Belgica. 8805 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10756 records from Collections of Bioclass, school #179, Moscow. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 337 records from MLZ Bird Collection (Arctos). 9 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 72965 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 34 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 140 records from Pat Livermore's Fungus Records 1976 - 2000. 3 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 15 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 1902 records from Midden-Limburg Fish Ponds Survey. 45948 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1798 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 548 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1803 records from AMAPPS Northeast Aerial Cruise Summer 2016. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 895 records from Geometridae de France métropolitaine. 18 records from Naturtag. 4799 records from Herbier Louis-Marie (QFA) - Collection de lichens. 16 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 11 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 9174 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 157 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 740 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1065 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1 records from Redescription of Luetkenia elongata (Copepoda: Siphonostomatoida: Pandaridae), an Ectoparasite of Luvarus imperialis (Actinopterygii: Perciformes: Luvaridae), with a New Record from Japanese Waters. 6 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 371 records from IOV-UDO-ZOOPLANCTON-PLAYA COLORADA. 120 records from BIRDRACE The early birds. 1933 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 20 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 2442 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 2430 records from Upper Silesian Museum, Bird Observations. 142 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 215 records from SEWBReC Springtails and allies (South East Wales). 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 63616 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 286 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 146 records from Données de la naturaliste Laurence Beauchamp. 164 records from Ladybirds of Ireland. 10 records from Collections ichtyologiques et herpétologiques (BOUM). 5074 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6141 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 78 records from Données de la naturaliste Anna Even. 11 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 2 records from A new species of crown-antlered deer Stephanocemas (Artiodactyla, Cervidae) from the middle Miocene of Qaidam Basin, northern Tibetan Plateau, China, and a preliminary evaluation of its phylogeny. 81 records from Kystfuruskoger i Tysnes og Fusa. 25 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 19 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 1372 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 50 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 6 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 4335 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 5 records from Living Cirripedia. 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 359 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 5 records from Taxonomic notes on the genus Sinodrepanus Simonis, 1985, with description of the male of S. falsus (Sharp, 1875) (Coleoptera: Scarabaeidae: Oniticellini). 218 records from Land and freshwater molluscs of Northern Spain. 3753 records from Données naturalistes de Charlotte PICARD. 1 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 1905 records from University of Nebraska State Museum Birds Collection. 19947 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 1 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 4820 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 1386 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 74931 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 82715 records from Fish specimens of Kagoshima University Museum. 464 records from UTEP Invertebrates (Arctos). 1227 records from Fish occurrence in Kuban River basin. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 6 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 756 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 10 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 3 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 213926 records from Phase 2 Lowland Grassland Survey of Wales. 5 records from Campodeidae (Hexapoda: Diplura) from Kyrgyzstan, Central Asia, with the description of a remarkable new genus and species. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 1575 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 970852 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 390001 records from DATAVES. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 14 records from Berea College, Ralph L. Thompson Herbarium. 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 104071 records from Fermanagh Flora. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 445 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 4 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 11 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 12 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 2732 records from Biodiversity of the Desna river valley and its tributaries. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 5 records from Loricifera - SMF. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 833 records from Plant species from the sacred and community forests of Mono departement. 342695 records from KTP Ring Data. 63 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 28758 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 34 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 143568 records from Movement patterns of Peruvian Boobies off Isla Lobos de Tierra 2006. 487 records from Birds Specimens. 94 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 12190 records from DMNS Mammal Collection (Arctos). 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 66 records from Tortugas Marinas del Golfo de California (aggregated per 1-degree cell). 64 records from Bats of northeastern Vietnam. 1028 records from IBF Monitoring of Fungi. 13 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1184 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1560 records from Pacific turtle tracks: Turtle-Safe Seas Project. 31 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 75 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 2 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 240 records from Knechtweide (Kohlfurth). 875 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 83 records from MCP-Mamiferos - Coleção de Mamíferos. 11 records from Benthic macrofauna abundance of sediment core 12930-073. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1735 records from Occurrence database of native plants and animals of south-central Chile. 259 records from Natura 2000 Parc naturel régional de Lorraine. 25 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 4 records from Two new species of Sweltsa (Plecoptera: Chloroperlidae) from China. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 22 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 1486 records from Helmintos parásitos de peces del sureste de México. 1654 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 34 records from Happywhale - Killer Whale in Arctic Ocean. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 2 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 51 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 1526 records from Données de la collection Rousset -1947-2013. 3 records from Aristolochia luudamcui (Aristolochiaceae), a new species from northern Vietnam. 75 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 12094 records from Amino acid addition experiment Metagenome. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 1290 records from Diversity of Spiders from Azorean Trails. 1 records from Colecção Entomológica IIA. 8979 records from United Kingdom National Whale Stranding Database 1913-2008. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 6606 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 97 records from Inventario de Hymenóptera; parasítica en México. 53 records from DMNS Egg Collection (Arctos). 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from A new species of Anteon from Zimbabwe (Hymenoptera, Dryinidae). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1785 records from 3Soil16S. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 54670 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 234 records from Insectes Hyménoptères Scollidés de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 736 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 238 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6189 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 140 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 1 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 24 records from Données de NICOLAS Vincent (SAPROX). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 2572 records from seawater metagenome Metagenome. 3806 records from Heliconiine Butterfly Collection Records from University of Cambridge. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 508 records from Northern elephant seals post-molting 2017 (aggregated per 1-degree cell). 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 170 records from Fish specimens of Toyama Science Museum. 121 records from Range table from ostracoda in ODP Hole 143-866B. 5846 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 99 records from Sonidos de la Ecoreserva Campo Rubiales (Puerto Gaitán, Meta) - Proyecto FIBRAS. 14443 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 28050 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 7 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 763 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 7 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 1953 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 67 records from Post-nesting migration of loggerhead turtles around Japan 2005 (aggregated per 1-degree cell). 12 records from Lepidoptera specimen database of Japan. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 130 records from BIRDRACE - The famous Grouse feat. The James. 7066 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 5 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 26 records from Two new Hottentotta species from Iran, with a review of Hottentotta saulcyi (Scorpiones: Buthidae). 12 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 62 records from Données naturalistes de BONCHE Jérôme. 304 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 7217 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 16 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 1715 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 47 records from Schulgelände (Wetter). 282 records from Deponie Klausdorf. 14972 records from Données Entomologiques A. HORELLOU 1988-2018. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 263 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 247 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 55 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1409 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1919 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 329 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 1 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 302 records from BioGIS - Reptiles - HUJ collections. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 585688 records from Flora Atlas N.T.. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 6425 records from WOLL AVH data. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 23 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 43 records from Six new species of Anthuridae (Peracarida: Isopoda) from the southern Mexican Pacific. 498 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 2714 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 106 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 3 records from Three new species of the subterranean genus Guiodytes from Guangxi, China (Coleoptera: Carabidae: Clivinini). 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 186 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 969 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 13 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 308 records from Rare plants database extract from Scottish Natural Heritage. 11 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 580 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 2 records from Brown University Herbarium. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19317 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 21 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 16 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 118670 records from Happywhale - Humpback Whale in North Pacific Ocean. 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 1 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 11 records from Inventaire et regroupement de données Natura 2000. 10 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 816 records from Línea base general de peces para el valle medio del Magdalena - VMM. 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 7 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 74 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 72 records from Total foraminifera counts of multinet POS231/3_MSN1332. 160 records from AVJNF: Søholt Storskov, amphibian survey. 101 records from Taxonomic study of the genus Tenupalpa Lee et Li, 2021 (Lepidoptera: Gelechiidae Thiotrichinae) from China, with descriptions of fifteen new species. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 154 records from Viabilidad de semillas dispersadas por fauna en la microcuenca Teusacá, Bogotá D.C.. 4546 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 5 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 67 records from Siphonaptera and Phthiraptera Recording Scheme - records verified via iRecord. 59 records from Schulgelände SGD/Viersen. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 365 records from Flora genérica de las gramíneas del estado de Tlaxcala. 49 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 4 records from Colección Palinológica del Herbario LIL (PAL-TUC-FML-Tucumán). 2 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 1 records from Natural History Museum Maastricht (NL) - Herbarium. 399 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 5066 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 161 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 1 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 45 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 4 records from Novedades taxonómicas en Campanulaceae neotropicales I: dos nuevas especies de Centropogon C. Presl de Venezuela. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 27 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 13 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 23 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 4307 records from Biomass and mortmass of woody vegetation in metal-contaminated areas (Southern Urals, Russia). 374 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 6 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 199 records from Happywhale - Leopard seal in South Atlantic Ocean. 370 records from HBRG Invasive Non-native Plants Dataset. 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 194 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 2496 records from Données des collections d'algues du MNHN. 1757 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 64 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 22742 records from Formidabel; Belgian Ants Database. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 1148 records from ABC event data for Nyika Plateau, Buma Hills. 16 records from Hazel Dormouse in Ireland. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 27 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 33358 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 4 records from Two new species in the Russula (Russulaceae, Basidiomycota) crown clade from Indian Himalaya. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 2378 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 8 records from A review of Dinetus Panzer, 1806 with descriptions of five new species and keys to world species (Hymenoptera, Crabronidae). 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 12 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 92 records from Сypripedium guttatum Sw. in the Komi republic. 632 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 9 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 146 records from Abundance of birds in the Lena Delta Region. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 54 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 7 records from Descriptions Of The Adult Male And Female Genitalia Of The Genus Osobenus Ricker (Plecoptera: Perlodidae). 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 191 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 2 records from Happywhale - Southern Right Whale Dolphin in South Atlantic Ocean. 62 records from artsprosjektet_48-13_monomyx. 9640 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 642 records from Colección Ornitológica de la Universidad del Valle. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 75 records from Happywhale - Bryde's whale in South Atlantic Ocean. 794 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 962 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 6042 records from The Fungal Literature-based Occurrence Database for the Southern West Siberia (Russia ). 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 62576 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 545 records from Zootaxa. 6775 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 6467 records from NBMB Herps. 1 records from A new species-group of Clubiona Latreille, 1804 and descriptions of four new species from Borneo (Araneae, Clubionidae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 214 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 10048 records from Index Site Surveys Data for Olympia Oysters, Ostrea lurida, in British Columbia – 2009 to 2017. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 1036 records from BUND - Dassower See (Lübeck/Dassow). 5 records from A northern range extension of a Canadian species of Special Concern, Dielis pilipes (Hymenoptera: Scoliidae), in the Okanagan Valley of British Columbia. 56560 records from Données naturalistes de Monsieur François FOURNIER. 404 records from NHMO DNA Bank Other groups collection. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 53315 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 279 records from Peces asociados a raíces de manglar en el PN Morrocoy, Venezuela. 4 records from IMMS Ridley 9 (aggregated per 1-degree cell). 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 343 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 48 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 8300 records from University of Michigan Museum of Zoology, Division of Birds. 561 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 811 records from Données naturalistes de AUNEAU Florent. 1806 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 494 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 4 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 25 records from Collection Graptolithina fossil SMF. 1 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 25934 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 9 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 2691 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 6427 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 6249 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 67 records from Relative abundance of ostracods in sediment core Sv09. 902 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 686 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 192 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 78233 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 6 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 8 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 7 records from A New Species Of Perlesta (Plecoptera: Perlidae) From North Carolina With Additional Records For North Carolina And Virginia. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 296 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 4142 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 142 records from Size of planktic foraminifera at CTD station PS55/083-1. 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 36280 records from R. L. McGregor Herbarium Lichen Collection. 24279 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 11033 records from Oregon Bee Atlas Survey Data: 2018. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 52 records from Birds Specimens of Akita Prefectural Museum. 171 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Données naturalistes de LE GLOANEC Vincent. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 557 records from Corn bunting breeding distribution in Scotland. 1210 records from NEFSC Marine Mammal Abundance Cruise 2004 Passive Acoustic Monitoring - Rainbow Click Detections. 900 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 71 records from Foraminifera species abundances from tow TT007_7-MOC13. 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 26071 records from Banded Iron Formation and Greenstone survey data. 230 records from Biometría peces Parque Nacional Natural La Paya. 38 records from Microzooplankton abundance and biomass at station TT045_19-3. 41 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 3 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 25 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 1 records from The genus Mytilina in China, with description of a new species (Rotifera: Monogononta: Mytilinidae). 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 1 records from Salvia robertoana (Lamiaceae), a new species from Oaxaca, Mexico. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae). 18 records from Anfibios presentes en el Cerro Jánano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Données espèces - Expertise IPE 79. 1448501 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 50 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 63 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 20 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 656 records from South American Antarctic Marine Biodiversity Literature. 12780 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 3 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1381 records from Fungi Collection. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 87 records from Données espèces - Expertise IPE 70. 802 records from Colección Entomológica Universidad Nacional de Colombia, Sede Palmira (CEUNP). 940 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 293 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 1272 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 3 records from A new species of snail-eating snakes of the genus Pareas Wagler, 1830 (Reptilia: Serpentes) from eastern Himalayas, India. 12 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 4571 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 152 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 1 records from Happywhale - North Atlantic Right Whale in North Atlantic Ocean. 35617 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 8 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 62 records from Zoo Frankfurt. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 623694 records from Fungal Records Database of Britain and Ireland. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 2 records from Two new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from Guizhou, southwestern China. 52 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 2030 records from La familia Asteraceae en México. Fase VI. 505 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 9965 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 607 records from CRESLI marine mammal observations from whale watch cruises 2000-2019. 128 records from Données espèces - Expertise IPE 10. 63 records from Marine gastropod distribution from patagonian shallow waters. 421 records from Expedición ornitológica en los municipios de Florencia y Morelia, (Caquetá) - BIO Alas, cantos y colores. 254 records from Distributional data on high altitude endemic taxa of vascular plants from western Balkans. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 12 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 10 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 19 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 18 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 13 records from The genus Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) from Maranhão State, northeastern Brazil. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 278 records from Gomex Sperm Whale Survey 2000. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 5 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 576 records from Zooplancton del estrecho de Bransfield y alrededores de Isla Elefante, verano austral 2019-2020, durante la VI Expedición Científica de Colombia en la Antártica. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 16 records from Dinoflagellate cysts of surface sediments. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 50 records from Données d'observation de phanérogames marines en Martinique. 1264 records from Grand Voyeux - Suivis scientifiques. 36 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 27 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 1 records from Toxorhynchites (Lynchiella) caatingensis sp. nov. (Diptera: Culicidae) from the semi-arid region of Brazil. 42 records from UWIZM Cnidarians. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 374 records from Coastal and Marine Species Database. 900 records from Convention Fédération française de golf - MNHN 2016-2019.. 136258 records from Tasmanian Museum and Art Gallery provider for OZCAM. 2 records from TTRS Mammals. 164 records from Marybio Foundation marine mammal shipboard sightings in Bahia San Antonio, Patagonia 2008-2010. 224 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 46 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 90 records from Bat diversity data by Formosan Golden Bat's Home. 1774 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 18 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 526 records from Eventos de monitoreo de la especie plaga Didymosphenia geminata en cuerpos de agua de la zona centro sur austral de Chile, Etapa I (2016 - 2017). 163 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 4 records from UTEP Fish (Arctos). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 76 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 96 records from Peces presentes en la colección ictiológica de la Amazonía Colombiana de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 295 records from Données de VINCENT Alexis (SAPROX). 12 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 52859 records from British Antarctic Survey Argos satellite tracking data. 3763 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, November 2017-October 2018. 19 records from An annotated checklist of Belgian Therevidae (Diptera, Asiloidea). 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Taxonomic notes on the Polistes stigma group (Hymenoptera, Vespidae: Polistinae) from continental Southeast Asia, with descriptions of three new species and a key to species. 231786 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 113 records from Total foraminifera counts of multinet M26/1_MSN844. 14 records from Taxonomic status of Macaronesian Eucyclops agiloides azorensis (Arthropoda: Crustacea: Copepoda) revisited - morphology suggests a Palearctic origin. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 583 records from Données du naturaliste Christian Desmier. 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1134 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 22 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 11 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 7986 records from Données naturalistes de Franck NOEL. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1 records from Systematic revision of Calligrapha s. str. Chevrolat (Coleoptera: Chrysomelidae, Chrysomelinae). 2 records from A new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India. 364 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 3277 records from BioGIS - Mammals - SPNI. 849 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 8 records from The Neotropical species of the genera Pseudespeson L, 1994 and Espeson S, 1882 (Coleoptera: Staphylinidae: Osoriinae). 7527 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 110 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 6054 records from Community Foundation for Ireland Records. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 20 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 6913 records from Collection of saproxylic and xylobiont Beetles. 386063 records from Compost microbe establishment and growth in agricultural soils. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 13 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 202114 records from National Benthic Inventory. 56 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 5 records from New records of two butterflies of the genus Polyommatus Latreille, 1804 (subgenus Agrodiaetus Hübner, 1822) (Lepidoptera: Lycaenidae) from Iraq. 1 records from New names for two Malagasy species of Canarium L. (Burseraceae). 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 18790 records from Tachinid Recording Scheme - GB and Ireland records. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 4607 records from Données de type contact en Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 50897 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 3 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 199 records from Demospongias de la Laguna La Restinga, Venezuela. 55 records from Galls on Beech Trees in Hainich, 2008. 1000 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 181351 records from Carnet B Lorraine. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 4 records from The Chinese species of the mealybug genus Neotrionymus Borchsenius (Hemiptera: Coccoidea: Pseudococcidae). 5 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 377599 records from Seasearch Marine Surveys in England. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 576 records from Collection Trichoptera - SMF. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 1 records from Happywhale - Long-finned Pilot Whale in North Pacific Ocean. 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 561 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 3644 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 618 records from Pollen analysis of sediment core GeoB6518-1. 26247 records from Arizona State University Hasbrouck Insect Collection. 697 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 170 records from Vascular Plant Specimens of the RYU Herbarium (Faculty of Science, University of the Ryukyus). 3286 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 25 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 10 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 1164 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 3 records from Happywhale - Adelie Penguin in Southern Ocean. 70561 records from MDFRC macroinvertebrate survey. 128 records from Inventaire des reptiles 2014. 39929 records from DIBA-Parc del Montnegre i el Corredor. 4752 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 130013 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 35 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1 records from On species of the genus Macrosaldula (Hemiptera: Heteroptera: Saldidae) of the Palaearctic Region, with description of M. graziae sp. nov.. 1134 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 7 records from Grundwasserlebensraum im Englischen Garten (München). 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 208 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 2 records from Dilatapalochrus gen. nov. - a new species and a new genus of soft-winged flower beetle of the tribe Apalochrini (Coleoptera: Malachiidae) from East Africa. 1 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 1 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 2115 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 157 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 422 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 2 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 61 records from Shrews of Poland. 8 records from Archaeal 16S Ribosomal RNA RefSeq Targeted Loci Project. 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 11488 records from Données naturalistes de Pascal Dupont. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 20829 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 2165 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 310 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 145 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 2 records from Wie viel Natur gibt es im Park?. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 598 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 935 records from MEXU/Flora de Oaxaca. 26801 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 5343 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2082 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 50 records from Arizona State University Lois B. O'Brien Collection. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 5 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 3192 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 4500 records from Ravensthorpe Range survey data. 4 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 5 records from Schulinnenhöfe (Gelsenkirchen). 1 records from The Italian species of the Chthonius ischnocheles group (Arachnida, Pseudoscorpiones, Chthoniidae), with reference to neighbouring countries. 2851 records from Données naturalistes d'Alain BERLY. 10377 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 3 records from Clitobius grimmi sp. n. from Egypt with notes on C. oblongiusculus (Fairmaire 1875) (Coleoptera: Tenebrionidae: Blaptinae). 5 records from Two new desma-less species of Theonella Gray, 1868 (Demospongiae: Astrophorida: Theonellidae), from the Great Barrier Reef, Australia, and a re-evaluation of one species assigned previously to Dercitus Gray, 1867. 722 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7484 records from Yoann_BLANCHON_2017_12_18. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de données Natura 2000. 12222 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 189976 records from Données de la flore d’Alsace (SBA). 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 41 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 10 records from Données naturalistes de Sophie COHEN. 696 records from the diversity of anammox bacteria in the subterranean estuary. 53 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 450 records from 2020_nsmk_smpl_sw_450. 24808 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 1 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 153 records from NEON Biorepository Zooplankton Collection (Unsorted Bulk Sample). 150 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 498 records from Bekkelag basin, Inner Oslofjord. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 2023 records from Composición florística y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 305 records from Phenological Center - Birds (Laplandskiy). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 609 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 522 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 16 records from Four Species of Dulichiidae (Crustacea: Amphipoda) from Japan, with the Description of a New Genus and Two New Species. 57 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 64691 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 253821 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 67743 records from Flore Franco-Belge. 15916 records from EAC - Herbário Prisco Bezerra. 29846 records from Marine Biological Sample Database, JAMSTEC. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 61547 records from Florida Keys Reef Visual Census 2010. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 153 records from annex1. 123 records from Total foraminifera counts of multinet POS247/2_MSN1377. 10 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 62 records from Rare vascular plant species in North-West of Kostroma region, Russia. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 4 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 10 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 1145 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 6 records from Four new species of the genus Pseudosubhimalus (Hemiptera: Cicadellidae) from the Indian subcontinent. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 22 records from Description of lithologic section units of IODP Hole 325-M0054B. 1638 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1885 records from AlgaTerra. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 12988 records from LPO_PACA_2017_12_18. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 147 records from HSU Vertebrate Museum Mammals Collection. 8 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 22 records from Revision and phylogeny of the genus Andocaeculus (Acari: Caeculidae) I: the A. weyrauchi species group. 4 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 37445 records from ADDOMEx. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 6010 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 21338 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 13 records from North Cyprus 2015 - Green Turtles (aggregated per 1-degree cell). 40 records from Sightings for Airborne Mine Neutralization System Aerial Monitoring in the NSWC PCD Study Area from October 2011, 2012. 12487 records from UTEP Insects (Arctos). 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 10 records from Données naturalistes de DURON Cyril. 2166 records from Collection Pisces SMF. 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 40337 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1232 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 11 records from Reptiles Specimens of Akita Prefectural Museum. 157 records from UWIZM Snakes. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 1593 records from The Lichen Flora of Serra de São Mamede Natural Park. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 6654 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 7 records from Données bibliographiques ASFRA. 1 records from Acropoma profundum, a New Species of Lanternbelly (Teleostei: Perciformes: Acropomatidae) from the Solomon Islands. 34 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 138 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 1268 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 2743 records from marine sediment metagenome Raw sequence reads. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 130 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 3 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 4 records from Herbarium Senckenbergianum (FR) - Protista. 12487 records from Florida Keys Reef Visual Census 1996. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 41715 records from Données de l'Observatoire de la Faune de Bourgogne. 8 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 4027 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 138444 records from Wild bees of Belgium. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 392 records from Hawthorne Canal Birdwatching Survey. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 20 records from 2019_nsmk_smpl_mm_20. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 195 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 178 records from Echinoderms from the Seaflower Biosphere Reserve. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 479 records from Royal British Columbia Museum Entomology Collection. 9 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 27 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 4166 records from Línea base general de hormigas para el valle medio del Magdalena - VMM. 7 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 2110 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5938 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 66 records from Loggerheads in the Tyrrhenian Sea (aggregated per 1-degree cell). 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 2981 records from Colección Entomológica CDMB. 6 records from NZCS Invertebrates New Collection After 1987. 1 records from Happywhale - Ringed Seal in North Atlantic Ocean. 5489 records from Lepidoptera (Specimens NRM). 13 records from Coleção de Coleoptera da Universidade de Brasília. 45 records from Natterjack Toads of Ireland. 98 records from Warnowtal (Rostock). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 4 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 88500 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 138 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 17112 records from Chrysomelidae beetle data from iRecord. 1066 records from Densidad poblacional para fauna medida por medio de cámaras trampa en los Valores Objeto de Conservación (VOC) del territorial Andes Occidentales. 14 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 64903 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 28 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 858 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos silvopastoriles - Unillanos 2019. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 1 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 125 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 7 records from New species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Malawi and South Africa. 3766 records from Benthic foraminifera distribution of sediment core GIK17957-2. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 230 records from Porifera diversity and distribution data in the Southern Gulf of Mexico. 84 records from Colección de Hongos del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 1 records from Description on Solitudes dushengi gen. et sp. nov. from Xinjiang, China (Araneae: Gnaphosidae). 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 4035 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 614 records from BID-Malawi-Geometridae-Biodiversity-Data. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 1 records from First record of the freshwater crab genus Esanthelphusa Naiyanetr, 1994 (Decapoda: Brachyura: Gecarcinucidae) from Myanmar, with the description of a new species from the Kayin State. 8 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 111 records from Birdrace-Uhulogen-Lippe. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 144 records from La familia Asclepiadaceae en México. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 370 records from Otter survey of Ireland 2004 & 2005. 3612 records from JOI - Herbário Joinvillea. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 18 records from A revision of the African wolf spider genus Amblyothele Simon. 1033 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1392 records from Happywhale - Gray Whale in North Pacific Ocean. 17 records from A review of Paratranes Zimmerman, 1994, Xanthorrhoea-associated weevils of the Tranes group (Coleoptera, Curculionidae, Molytinae), with description of a new species. 4 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 6 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 57629 records from NINA Vanndata fisk. 4 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 510 records from Inventaires des cygnes du département de l'Eure. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 39 records from Inventaire Faune. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 29 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 208 records from Registros de arañas en el marco del proyecto Influencia de la dieta sobre la toxinología y toxicología en arañas. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 17827 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 6 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 4600 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 1514 records from Gemeinde Sursee. 5 records from Review of the genus Shilovia Makarchenko (Diptera: Chironomidae: Diamesinae Boreoheptagyiini) from the mountains of Central Asia, with morphological description and DNA barcoding of known species. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 525 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 852 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 221 records from Acoustic detections from R/V Song of the Whale during the spring 2019 MAPS survey (NMFS permit 14809). 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 829 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 90 records from NMML Harbor Porpoise Aerial Survey, Kodiak Island, Replicate 3, 1992. 3 records from Taxonomic noteson thegenusPseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae Eumeninae) from Vietnam with key to all known species in the Oriental region. 1 records from SFSU - Vascular Plants of the Harry D. Thiers Herbarium at San Francisco State University. 1 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 265745 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 7 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 1 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 23 records from 2017 Onwards Rare Invertebrates in the Cairngorms Northern Silver Stiletto Fly Survey Data. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 18756 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 4510 records from NCSM Mammalogy Collection. 16 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 84 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 151 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 2191 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 3 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 5 records from Diversity and distribution of North Atlantic Lepechinellidae (Amphipoda: Crustacea). 7191 records from Colección general del plantas vasculares del Herbario JBB. 86676 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 160 records from Seabird sightings in Ghana and Ivorycoast. 206796 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 3 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 71 records from Avifauna asociada al área boscosa del resguardo indígena Cuti, municipio de Unguía, Chocó. 2020. 104 records from Cowan Tetrapod Collection - Herpetology. 147 records from Total foraminifera counts from multinet M31/3_MSN898. 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 1329 records from Royal Belgian Institute of Natural Sciences Mammal collection. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 29 records from Hemmerder Schelk (Unna). 1 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 28015 records from Elephant Seal Sightings, Macquarie Island. 254 records from A monograph of the genus Maladera Mulsant & Rey, 1871 of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini). 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 280 records from Butterflies of Singapore and Peninsular Malaysia (Lycaenidae). 1972 records from All herbarium specimens of grasses held at TAN herbarium. 1 records from A taxonomic note of Pterocephalus (Caprifoliaceae) from N Iran. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 548 records from Pollen counts of sediment core GeoB9503-5. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 100 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 331 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 124 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 309 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 3 records from A new species of Cyrtodactylus Gray (Squamata; Gekkonidae) from the Thai Highlands with a discussion on the evolution of habitat preference. 270083 records from Parc_National_de_Port_Cros_2017_12_18. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 18112 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 11 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 646 records from MAG Herbarium: collections of vascular plants. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 25 records from Happywhale - Crabeater Seal in Southern Ocean. 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 85 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 25 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 31 records from The genus Coenosia Meigen in Iran, with a key to species and description of a new species (Diptera: Muscidae). 3886 records from Colección Carcinológica de Yucatán. 22 records from Satellite Tracking of Hawksbill Turtles in Melaka, Malaysia (aggregated per 1-degree cell). 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 11 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (1), 2010 - Données faune. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 5874 records from FrogWatch SA. 99 records from Nanoplankton abundance at station GeoB2006-4. 33 records from Données naturalistes de Françoise SERRE-COLLET. 2 records from Happywhale - Galpagos sea lion in South Pacific Ocean. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Données naturalistes de Monsieur LEFEBVRE François. 22 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from Bopopia, a new monotypic genus of Gesneriaceae (Gesnerioideae, Coronanthereae) from New Caledonia. 78 records from Spain-Baleric Is. 2015 Loggerhead Turtles (aggregated per 1-degree cell). 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 1211 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1338 records from Kallisti Limnes subsea pools Metagenome Study. 8 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 576 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from Two new species of the genus Tylostega Meyrick, 1894 (Lepidoptera: Crambidae) from China, with a list of all the known species in the world. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 163 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 6 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 159 records from Total foraminifera counts from multinet M31/3_MSN915. 41676 records from Tagged Seal Location Data from SOGLOBEC. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Majidae crabs from Morrocoy National Park - Venezuela. 333 records from Données naturalistes de Renaud PUISSAUVE. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 839 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 6 records from Marine algal (seaweed) flora of Faial Island, Azores. 8 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 13 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 2 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 651 records from Réseaux écologiques/Trame verte et bleue. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 2 records from Additions to the deep-sea echiuran (Echiura) fauna of the North-East Atlantic. 4 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 370 records from Otter (Lutra lutra), Outer Hebrides. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1510 records from Leif Richardson Vermont Bee Specimens. 3 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 2628 records from Collection Crustacea - ZMB. 416 records from The Living Murray Fish data. 643 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 1 records from Phylogenetic relationships based on morphological data and taxonomy of the genus Salvadora Baird & Girard, 1853 (Reptilia, Colubridae). 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 10 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 25974 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 1 records from Le genre Oxyanthus DC. (Rubiaceae) en Afrique de l’Ouest: description d’une nouvelle espèce. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 2 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 240 records from BARTH-Environnement_2017_12_18. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 156 records from Total foraminifera counts of multinet M21/2_MSN658. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 5 records from Phytoseiid mites of Slovenia (Acari: Mesostigmata): new records and first description of the male ofAmblyseius microorientalis. 13 records from New State Records Of Kentucky (Usa) Stoneflies (Plecoptera). 34 records from Microzooplankton abundance and biomass at station TT043_11-1. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 22 records from Five new and five known species of the genus Tylencholaimus de Man, 1876 (Nematoda: Dorylaimida: Tylencholaimoidea) from Western Ghats of India. 49 records from Ghent university - Zoology Museum - Nematod Collection. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 101 records from BIRDRACE Enger am Spektiv. 12 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 125 records from Total foraminifera counts from multinet M32/3_MSN956. 6164 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Données naturalistes de CLERGET sylvie. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 13 records from Warnowufer Groß Klein. 7 records from Stadtrandlandschaft Apolda-Nord. 25 records from Algas pardas (Ochrophyta: Phaeophyceae) de la colección ficológica "Germán Bula Meyer", de la Universidad del Magdalena. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 6 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 375 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 29 records from Sea Turtles of Nicaragua's Pacific Coast (aggregated per 1-degree cell). 6 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1351 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 1814 records from UKSBA Cyprus - Habitat Samples, 2019. 102325 records from Herbarium of Taiwan Forestry Research Institute. 90 records from Swedish Malaise Trap Project (SMTP) - Pallopteridae. 11 records from ALP-PAGES_2017_12_18. 23 records from Ackerrain Plönhagen. 6467 records from Colección Herpetológica (Anfibios) del Museo de Historia Natural de la Universidad Industrial de Santander. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 143 records from Malawi-Histeridae-Biodiversity-Data. 1992 records from Actualización de la base de datos de la Colección Regional Durango (Tejido). 4 records from Delturinae, a new loricariid catfish subfamily (Teleostei, Siluriformes), with revisions of Delturus and Hemipsilichthys. 18 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 1 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 1 records from A new species of Cofana associated with grasses from India (Hemiptera: Cicadellidae: Cicadellinae). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 22 records from Bachabschnitt der Nette (Osnabrück). 17244 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos de bosque 2013 - 2017. 109615 records from Santa Barbara Museum of Natural History Entomology Collection. 358 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 1567 records from Occurrence of wild and cultivated yams observed in West Africa and Madagascar from 1996 to 2015. 1 records from New species of Chaetonerius Hendel (Diptera: Neriidae) from the Oriental Region. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 21166 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 23 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 19 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 2145 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 1417 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 4 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 81848 records from CAS Botany (BOT). 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 2225 records from Données naturalistes d'Anaïs MAS. 1 records from A new genus of Oxypodina from Kyrgyzstan (Coleoptera, Staphylinidae, Aleocharinae, Oxypodini). 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 5 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 61 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 508 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 9704 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 129 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 283 records from Flux data of NU2_trap (Table A1). 2068102 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 830 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 178 records from (Fig. 3) Relative abundance of Neogloboquadrina pachyderma (s) in sediment core MD99-2343. 3 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 69 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 598 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 5346 records from Sediment metagenome. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 4 records from Two new species of Nealiolus Mason (Hymenoptera, Braconidae, Brachistinae) reared from pest weevils (Coleoptera, Curculionidae). 2 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annobón Island, Gulf of Guinea. 26 records from Happywhale - Blue Whale in Southern Ocean. 9022 records from Happywhale - Humpback Whale in North Atlantic Ocean. 2 records from First record of the genus Phanoperla Banks, 1938 (Plecoptera: Perlidae) from mainland China, with description of a new species. 21 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 405 records from Línea base general derivada de sonidos unidireccionales (espectro audible) para el valle medio del Magdalena - VMM. 4 records from A new species of Leptobrachella (Anura: Megophryidae) from southern Guangxi, China. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 32 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 653 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 4 records from Données naturalistes de Stéphane ORIO. 260 records from Miljodir_naturtypekartlegging_2017. 298 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3868 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 2 records from Proguithera caspersi, a new cavernicolous thread-legged bug species (Hemiptera Heteroptera: Reduviidae: Emesinae) from Hainan, China. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 257 records from Deep-sea megabenthos of the Eurasian Central Arctic based on image analysis.. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 7 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 8 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 11973 records from CPAP - Herbário CPAP. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 14 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 134 records from Rare species of plants in the southern part of the Sinyukha river basin. 7 records from Harpactus Shuckard. 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 602 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 2165 records from Jardín Botánico Atlántico, Gijón: JBAG. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 91 records from Données de la naturaliste Marie Melun. 51 records from Données du naturaliste MARCHAL Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 1419 records from Diversity of algae in wetlands. 100 records from AFAST Hatteras Aerial Survey -Left side- 2011-2012. 438 records from NEON Biorepository Terrestrial Plant Collection (Litterfall). 3645 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 2 records from A new species of freshwater crab of the genus Strengeriana Pretzmann, 1971, from El Jardín Natural Reserve, Quindío, Colombia (Crustacea: Decapoda: Pseudothelphusidae). 305 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 4 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 40100 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Vascular Plant Herbarium. 4 records from Open-holed trapdoor spiders of the genus Teyl (Mygalomorphae: Nemesiidae Anamini) from Western Australia’s Pilbara bioregion: a new species and expanded phylogenetic assessment. 5 records from Four new species of the genus Cratospila Foerster (Hymenopter, Braconidae, Alysiinae) from South Korea. 306 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 2 records from A new macromedusa from the coast of Mozambique: Aurelia mozambica sp. nov (Scyphozoa: Ulmaridae). 3 records from Abundance of zooplankton in the Aral Sea. 11193 records from Baselines Initiative 16S rRNA gene dataset: Baselines Amplicon Release 1 (R1) Caribbean Sea near Curacao (including saline pond samples in Curacao) 2015. 3 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 88 records from Noosa Shire Nature Map. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1389 records from Phytoplankton abundance in surface water during cruise CD61. 1 records from Endogean and Cavernicolous Coleoptera of the Balkans. XXIII. A new species of Paramaurops J. Müller (Coleoptera: Staphylinidae: Pselaphinae) from Greece. 614 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 6926 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1792 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 25 records from Biological Collection, National Institute of Oceanography, Goa, India. 83970 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 31 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 64 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 21458 records from Weevil and Bark Beetle records via iRecord. 92 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 12 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 93 records from Données du/de la naturaliste Fourrier Thibault provenant de la base de donnée du SINP Île-de-France CETTIA. 48 records from Stigmella stettinensis (Nepticulidae) specimen data. 282 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 735 records from Plants of the Botanical Garden of Surgut State University (Surgut, Russia). 23 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 11 records from Benthic macrofauna abundance of sediment core 13200-045. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 2217 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 59 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 2087 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 1 records from Pitcairnia albifolia (Bromeliaceae), a new species from the Talamanca Mountains in Veraguas Province, Panama. 8158 records from Dark ocean microbial diversity. 2000 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 3 records from Taxonomic review of the genus Assamacris (Orthoptera: Acrididae: Catantopinae) with a new species and a newly discovered female. 8 records from pbzt_insect_biodiversity. 80 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 148 (N.S) n° 41 (1), 2013 - Données faune. 7 records from Insect specimens of Himeji City Science Museum. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 2 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 217 records from NZCS Upper Tapanahony Expedition 1991. 97 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 1 records from Description of the female of Chelis ferghana Dubatolov, 1988, an endemic moth species of the Tien Shan Range in Central Asia (Lepidoptera: Erebidae Arctiinae). 147 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 1 records from A new Himalayan species of Alfieriella (Coleoptera: Cryptophagidae). 1 records from Fish specimens of Natural History Museum, Kishiwada City. 7 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 347 records from Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 97 records from Plantación de árboles nativos con fines de restauración en el departamento de Cundinamarca, como parte de la iniciativa 180 millones de árboles nativos. 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 2326 records from DEMNA-DNE : Freshwater mussels occurrences in Wallonia. 5 records from Labiobaetis Novikova & Kluge in West Africa (Ephemeroptera, Baetidae), with description of a new species. 1 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 11387 records from 16S data from: Diversity of Pico- to Mesoplankton along the 2000 km Salinity Gradient of the Baltic Sea (Hu et al. 2016). 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 53 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 29 records from Naturerfahrung. 158 records from Total foraminifera counts from M35/1_MSN1047. 937 records from Données naturalistes de Damien Combrisson. 2214 records from Range table from benthic foraminifers in ODP Hole 159-962D. 6652 records from Inventory of plant species through Benin (West Africa). 31 records from Synopsis of the Asian species in the genus Zarcosia Collado & Alonso-Zarazaga 1996 with new combinations and descriptions of fourteen new species. 19 records from Suivi des reptiles des landes du Technopôle du Madrillet. 896 records from Data on agroforestry plant species of Benin. 29 records from Données malacologiques du site Natura 2000 de Cessière-Montbavin. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 4 records from A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand. 3449 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 2 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 14 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 21 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 2 records from A New Iranian Species Of The Subgenus Labidostoma (Prostigmata: Labidostomatidae), With New Biogeographic Data On The Integrum Species Group. 2 records from A review of the Barsine perpallida-B. yuennanensis species-group, with descriptions of six new species (Lepidoptera: Erebidae: Arctiinae). 2011 records from UNCW Right Whale Aerial Surveys 2008. 11 records from Benthic macrofauna abundance of sediment core 13078-013. 1 records from A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides. 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 4 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1296 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 1 records from A new species of Aphantolana Moore & Brusca, 2003 (Crustacea: Isopoda Cirolanidae) from the Andaman Islands, northern Indian Ocean. 21 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 2 records from Yunnan-Guizhou Plateau: a mycological hotspot. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 168 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 661 records from Données espèces Expertise IQE 311. 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 1 records from Amphilochidae *. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 15130 records from MMS Surveys, SCB 1995-1997. 75436 records from India Biodiversity Portal publication grade dataset. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 3 records from Discovery of a new species of Lacon Laporte (Coleoptera: Elateridae: Agrypninae) endemic to Cyprus, with a modified tarsal morphology. 29 records from Total foraminifera counts of trap L3_92_45. 1736 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 88 records from "Schlechteberg" Ebersbach/Sa.. 43 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 3 records from Impatiens wutaishanensis (Balsaminaceae), a new species from Southeast Yunnan, China. 24 records from 2019_nsmk_smpl_ms_20200603. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 107 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 1100135 records from Estonian Naturalists’ Society. 1 records from Longhorned woodboring beetles (Coleoptera, Cerambycidae) from Cusuco National Park, Honduras: new species, new records, and revalidation. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 2 records from Revision of the troglomorphic genus Troglostygnopsis Šilhavý, 1974 (Opiliones, Laniatores, Stygnopsidae). 10 records from A new species and a new record of Eupines King from China and Japan (Coleoptera Staphylinidae, Pselaphinae). 119 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 2 records from Hawksbill turtle - Milman Island (aggregated per 1-degree cell). 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 191 records from sediment microorganism Metagenome. 64 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 673 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano (Larvas de peces). 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 237 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1093 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 397 records from Revision of Chondrocyclus s. l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species. 13 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 4 records from A new medium-bodied rupicolous Hemidactylus Goldfuss, 1820 (Squamata Gekkonidae) from the Sirumalai massif, Tamil Nadu, India. 165 records from Large ants are not easy - the taxonomy of Dinoponera Roger (Hymenoptera: Formicidae: Ponerinae). 385 records from Eufáusidos norte de Chile. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 32850 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 335 records from Registros de almeja (Polymesoda arctata) en la Ciénaga de pajarales. 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 18 records from "Biodiversidad en el valle de Cuatro Ciénegas". (Ácaros acuáticos). 106 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 17 records from Peces de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 22983 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 3 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 52801 records from Finnish Floristic Database (Literature Sources). 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 1 records from A new species of Nasusina Pearsall from Colorado (Lepidoptera: Geometridae: Eupitheciini). 2 records from Two new freshwater species of Bacillaria (Bacillariophyta) from Dongting Lake, China. 52378 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 31298 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 230 records from Inventaire avifaune. 2 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 36705127 records from iNaturalist Research-grade Observations. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 1 records from Lysimachia rupestris F. H. Chen & C. M. Hu (Primulaceae): a new record for the flora of Vietnam and reconsideration of its taxonomical position. 1 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 1 records from Capalictus, a new subgenus of Lasioglossum Curtis, 1833 from South Africa, with description of three new species (Hymenoptera, Apoidea, Halictidae). 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 16024 records from Inventaire des Mammifères marins de France (métropole et outre-mer). 30 records from Bohemannia auriciliella (Nepticulidae) specimen data. 12 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 1 records from A new species and key to all known species of Confusacris Yin & Li, 1987 (Orthoptera: Acrididae) from China. 70263 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2018. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 515 records from Outer Hebrides Insect Records from Literature. 4105 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 241 records from Molluscus specimens of Toyohashi Museum of Natural History. 24 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 24940 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-Río San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 5692 records from Phenology and biological traits of adult migrating shad (Alosa sp) sampled by trapping in the survey in the Nivelle river (France). 5 records from A new species and the phylogeny of the South American genus Gromphas Brullé, 1837 (Coleoptera: Scarabaeidae: Scarabaeinae: Phanaeini). 688 records from données arachnologiques de CARR David. 73 records from NMML Harbor Porpoise Aerial Survey, Kodiak Island, Replicate 1, 1992. 40 records from Two new species of Ecpatia Turner, 1902, and the first records of Ecpatia sciachroa Hampson, 1926 and Ecpatia obscura Holloway, 2009 from Thailand (Lepidoptera: Noctuidae, Noctuinae). 1690 records from Passive acoustic monitoring of killer whales in the northern Gulf of Alaska. 48 records from Ruhrwiesen bei Neheim-Hüsten. 293 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 50048 records from Fungi of Costa Rica (INBio). 270 records from ABC Matandwe Forest Reserve Vegetation Survey. 154 records from MIRC NAVFAC MISTCS Vessel Surveys Jan-Apr 2007. 30981 records from Intermountain Herbarium (Vascular plants & algae). 16 records from Two new species of the Tenthredo grahami group from China (Hymenoptera: Tenthredinidae), with a revised key to species. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 1873 records from Microbial community structure of chronically polluted marine sediments from a cold region of the southern hemisphere. 91352 records from 臺灣兩棲類資源調查與教育宣導推廣計畫 Resources survey and education advocacy to promote for Taiwan amphibian resources. 1 records from Laximicracis-a new genus of Afrotropical Micracidini beetles (Coleoptera Scolytinae). 134 records from BIRDRACE Griffin Wood Warblers. 184 records from Kystfuruskoger 2015. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 230 records from Nephtyidae (Annelida: Polychaeta) from the Sea of Marmara and Black Sea, with descriptions of two new species. 91 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 3 records from A contribution towards checklist of fungus gnats (Diptera, Diadocidiidae, Ditomyiidae, Bolitophilidae, Keroplatidae, Mycetophilidae) in Georgia, Transcaucasia. 4 records from Two new species of the genus Sinopodisma (Orthoptera: Acridoidea: Catantopidae: Podisminae) from China. 65 records from Inventaire biodiversité du site Pierre Fabre de Castres La Chartreuse. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 2 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 8 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 15 records from Taxonomy of the sea stars (Echinodermata: Asteroidea) from Bahia State, including ontogenetic variation and an illustrated key to the Brazilian species. 11 records from Sphyraena stellata, anew barracudafromthe Indo-Pacific, with redescriptionsofS. helleri Jenkins, 1901 and S. novaehollandiae Günther, 1860 (Perciformes: Sphyraenidae). 1301 records from Esponjas asociadas a raíces de Rhizophora mangle del Parque Nacional Morrocoy. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 690 records from Project for Reef Fish Monitoring. 40 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 66 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 4124 records from Inventaire de la flore des ENS des Pyrénées-Atlantiques 2011-2012. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 4376 records from JCT AVH data. 35 records from Macrohongos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 27430 records from Hymenoptera collection of the Finnish Museum of Natural History. 907 records from JOIw - Xiloteca Joinvillea. 324 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 502 records from AMAPPS Southeast Aerial Cruise Spring 2014. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1319 records from Inventaire et suivi Avifaune. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 459 records from Marine Mammal Observation - Total Denmark 2013-2020. 1 records from A new species of Sphaeridium from northeastern India and Myanmar (Coleoptera: Hydrophilidae: Sphaeridiinae). 43 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 6 records from A new species of Notacanthurus Tshernova, 1974 (Ephemeroptera: Heptageniidae) from India. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 1 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 16 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 694 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 25 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 13723 records from Harbour seals GPS telemetry in Baie du Mont Saint-Michel. 8709 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 13 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 487 records from NEON Invertebrate Voucher Collection at Arizona State University. 589 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 34 records from Review of the plant bug tribe Eccritotarsini (Hemiptera: Heteroptera: Miridae) of India and Sri Lanka with description of two new genera and six new species. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16361 records from Database for alien invasive plants occurrences in Germany. 34 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1326 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 337 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 115 records from Strathclyde badger sett surveys 1996-2000. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 4341 records from OUPR - Herbário "Professor José Badini". 2017 records from Flore des reliques forestières de la commune de Dangbo. 1 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 1 records from Happywhale - Harbor Seal in Southern Ocean. 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 283 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 11757 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 68 records from Chronicle of Nature - Phenology of Mushrooms of Baikalsky State Nature Biosphere Reserve. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 2 records from California State University, Long Beach Mammals. 28 records from Royal Saskatchewan Museum - Ichthyology Collection. 240 records from Tejidos de individuos colectados en el plan de monitoreo de biodiversidad en el bloque platanillo de la empresa Amerisur y en los bloques Rumiyaco, Venados y Burdyne de la empresa Gran Tierra, Putumayo. 981 records from Monitoreo de la ocupación del Oso Andino (Tremarctos ornatus) en el Parque Nacional Natural Chingaza. 2735 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 92 records from Nottekanal, Klasse 7 - 10. 28 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 810 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 14548 records from données aranéologiques de CORNIC Jean-François. 8 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 48 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from Systematics and convergent evolution in three Australian genera of Pepsinae spider wasps (Hymenoptera: Pompilidae). 3547 records from Clare Biological Records Centre Dataset 2004-2007. 1582 records from 2020_biodiversity_information_specimen_cnu. 845 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 5 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 2 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 8 records from UMNH Reptiles and Amphibians Collection (Arctos). 2103 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 324 records from CNAN/Scorpiones. 1 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. VII. A new species of Dieidolycus Anderson, 1988 from the Bismarck Sea. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 491 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 3 records from A supplemental description of the genus Lista Walker from China (Lepidoptera: Pyralidae), with two new and a newly record species. 46736 records from Mangroves of the Northern Territory, 1:100,000, Australia (1996). 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 19539 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 254 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 114 records from BIRDRACE Di-Bi-Di-Birder. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 6 records from A new species of the genus Liljeborgia Spence Bate, 1862 (Crustacea: Amphipoda: Liljeborgiidae) associated with the burrows of the spoon worm Urechis unicinctus in the Sea of Japan. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9470 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 63 records from Données du/de la naturaliste Champagne Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae). 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 25 records from Butterflies of Singapore and Peninsular Malaysia (Pieridae). 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 182 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 243 records from Thistles species and abundance. 201 records from Total foraminifera counts of multinet SO118_MSN1253. 5598 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 9 records from Additional notes on Psychotria (Rubiaceae) from the southern karst of Papua New Guinea: P. defretesiana comb. et stat. nov., P. dieniensis var. banakii var. nov., and P. stevedarwiniana sp. nov.. 29559 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 1629 records from Flora vascular acuática de la cuenca del Río Tamesí. 2 records from A new species of Pseudobunocephalus Friel, 2008 (Siluriformes: Aspredinidae) from the lower Tocantins and Mearim river drainages, North and Northeast of Brazil. 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 2 records from A new species of square-headed wasp Dasyproctus Lepeletier & Brullé (Hymenoptera: Crabronidae: Crabronini) from India, with notes on its biology. 4 records from Olbiogaster Osten Sacken (Diptera: Anisopodidae) from Mexico, with the description of three new species. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 45 records from Global diversity and distributions of symbiotic copepod crustaceans living on octocorallians. 4 records from Black grouse lek survey in Wester Ross and Skye 2009. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 160 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 81 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 23 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 463 records from Caracterización de la fauna y flora presente en los predios propuestos para el plan de restauración del distrito de conservación de suelos del cañon de rio grande (DCS-CRG), en el municipio de Dagua. 54 records from VFD-H: MIttelgebirgsweide. 339 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE218. 88 records from Microzooplankton abundance measured on water bottle samples at station PS65/587-1. 206 records from Amphibiens de Guyane. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 6 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 2 records from Two new species, including one representing a new genus, of the West African millipede family Campodesmidae (Diplopoda: Polydesmida). 32 records from Smear slide analysis on sediment core GeoB4206-1. 45 records from Happywhale - Fin Whale in South Atlantic Ocean. 4 records from Collection Myriapoda - SNSD. 47481 records from Dreal Corse - Base Ogreva. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 33043 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 2 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 1141 records from Tethys Research Institute aerial survey cetacean sightings 2009-2011. 4 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 14 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 12 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 1895 records from Dorset SW Pilot species dataset. 30 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 6 records from Occurrence data of dragonflies available at the National Museums of Kenya's Natural History Collection, Invertebrates Zoology Section.. 3 records from A redescription and a synonym in the South Asian millipede genus Xenobolus Carl, 1919 (Spirobolida, Pachybolidae). 333 records from Macroinvertebrados acuáticos asociados a humedales urbanos del municipio de Quibdó - Chocó, 2019. 84 records from BIRDRACE Bielefinken. 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 32 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 35 records from Inventaire et suivi de la faune écrasée. 24 records from Microzooplankton abundance and biomass at station TT043_7-20. 1000 records from nsmk_mm_2019. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 21 records from Chronicle of Nature - Phenology of Arachnids of Visimsky Nature Biosphere Reserve. 112 records from Caracterización de Flora de la Reserva Forestal Protectora Regional Brisas del Rincón. 16289 records from Vegetation of the Rybachy Peninsula and the Sredny Peninsula, Murmansk Oblast, Russia. 687 records from gas hydrate bearing sediment Raw sequence reads. 1667 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 450 records from 2020_nsmk_smpl_pl_450. 111 records from Données espèces - Expertise IPE 15. 13 records from A new Ovia species (Araneae, Lycosidae) from Singapore, with the transfer of Pardosa alboannulata Yin et al., 1997. 540 records from Diatom assamblage in samples from sediment trap OG4. 172 records from DAR AVH data. 3 records from Seven new species of the cicada genus Guyalna Boulard & Martinelli, 1996 (Hemiptera: Cicadidae: Fidicinini) with a re-description of the type species. 10 records from Happywhale - Commerson's Dolphin in South Atlantic Ocean. 345 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 148062 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 1 records from A new macropterous genus with a new species of Vianaididae (Heteroptera, Tingoidea, Vianaididae) from Peru. 161 records from Swedish Malaise Trap Project (SMTP) - Rogadinae. 698 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 7 records from New tax
Keywords: GBIF; biodiversity; species occurrences